Program of activities to encourage motivation for the profession of students who enter the agronomy career at the University of Cienfuegos - Rivero Casanovas , Caridad Josefa; Mesa Reinaldo, José Ramón; Cuellar Valero, Eligia de la Caridad; Sánchez Rivero, Richard Darian (Revista Minerva, 2021)
In order to design a programme of activities to encourage motivation by the profession os students entering the Agronomy career in the University of Cienfuegos, the present study was developed during the couses 15-16 to 17-18. Teaching from the university classroom should be a precess of helping the students to achive their personal maturity and promote from the free development of their profesional capabilities, so it is vital to promote form the teaching process motivation for the profession as an indesoensable element to training profesional they recieve. The initial diagnosis made to fist year group allows know the level of motivation students are entering the career. A proposed that includes actions to make changes to the preparation of the subjects of the first year, the preparation activities of the teacher to work the profesional motivation and a programme of activities is proposed to encourage motivation of the students for the course they are studying, which are incorporated into the planning course teacher. Finally, the evaluation of the course is carried out and presented and discussed the results achieved with your application.